Environmental sampling for Listeria monocytogenes control in food processing facilities reveals three contamination scenarios. (May 2015) - Muhterem-Uyar, Meryem; Dalmasso, Marion; Bolocan, Andrei Sorin; Hernandez, Marta; Kapetanakou, Anastasia E.; Kuchta, Tomáš; Manios, Stavros G.; Melero, Beatriz; Minarovičová, Jana; Nicolau, Anca Ioana; Rovira, Jordi; Skandamis, Panagiotis N.; et al.
Abstract: Listeria monocytogenes enters the food processing facility via environment, or contaminated raw materials. To increase the understanding of L. monocytogenes environmental contamination in the meat and dairy food sector, six European scientific institutions sampled twelve food processing environments (FPEs) in a harmonized methodological approach. The selection of six previously assumed uncontaminated (UC) FPEs and six contaminated (C) FPEs was based on the L. monocytogenes occurrence information originating from the time prior to the current study. An aim of the study was to highlight, that FPEs regarded for years as uncontaminated, may also become L. monocytogenes contaminated and repeated environmental sampling could help to identify the potential sources of contamination. From a total of 2242 FPE samples, L. monocytogenes was present in 32% and 8.8% of meat and dairy processing environments, respectively. In the actual study, each FPE was contaminated with L. monocytogenes on at least one sampling occasion. Three contamination scenarios could be observed: (i) sporadic contamination in the interface of raw material reception and hygienic areas, (ii) hotspot contamination in the hygienic processing areas (iii), and widely disseminated contamination in the entirely FPE. These data demonstrate that L. monocytogenes are common colonizers of FPEs in the European processing facilities sampled and that a consistent cross-contamination risk exists. To avoid food contamination, a risk assessment approach should assign risk levels to critical control areas (CCAs) and identify those where cross-contamination should be essentially excluded. Highlights: Twelve European food processing environments (FPEs) were sampled for the presence of L. monocytogenes . L. monocytogenes was present in 32% and 8.8% of meat and dairy processing environments. Each FPE was contaminated on at least one sampling occasion. Sporadic, hotspot or widely disseminated L. monocytogenes contaminations were observed.